Female Directors, Family Firms, Climate Talk and Climate Walk: European Evidence - Niklas Bergmann; Patrick Velte; Ignacio Requejo (Business Strategy and the Environment, 2025)
Growing attention is attributed to symbolic and substantive climate efforts, labelled as climate talk and walk. Focusing on the European capital market, we study the relationship between board gender diversity, family ownership and different levels of corporate climate activities along the continuum from climate talk to climate walk. Using emission reduction target data from the Carbon Disclosure Project (CDP), we conduct various panel regression analyses and propose several additional robustness tests. Our results extend prior research on carbon performance and reporting by providing novel insights into how firms translate their climate ambitions into actionable targets and how they subsequently deliver on those targets. This study stresses that firms with gender-diverse boards engage more in symbolic climate talk but not in substantive climate walk. Empirical evidence on the family ownership impact is mixed. Overall, family ownership tends to exhibit a negative association with climate actions, although the effect depends on the ownership concentration threshold and varies with family management. Our results also indicate that female directors mitigate the negative direct consequences of family ownership for climate actions. Our study contributes to the ongoing discourse regarding symbolic and substantive climate efforts among European businesses and sheds light on the particular role of different corporate governance mechanisms for attaining international climate objectives. As climate-related regulatory initiatives unfold rapidly, the results are highly relevant to European firms, their stakeholders and regulators. In terms of their practical application, our results may inform the pending `omnibus' proposals to revise European sustainability legislation while also helping firms to reflect on their governance structures in line with climate needs.
Keywords: 650; board composition; board gender diversity; carbon performance; carbon reporting; climate targets; corporate governance